“Baptism of Repentance for the Remission of Sins”: Mark 1:4 in Its Context - Malina, Artur (The Biblical Annals, 2021)
The titular term commonly refers to the baptism administered by John. In the other earliest sources, forgiveness of sins is not closely linked to washing with water performed by him, as the description of the Baptist’s appearance in the Gospel of Mark seems to suggest. The analysis of the verse marked in the title leads to the conclusion that Mark characterizes John’s appearance by two conjoined activities: baptizing and preaching which are expressed by the participles βαπτίζων and κηρύσσων. The first one allows for diagnosing the state of relations between humans and God. This diagnosis is expressed through the confession of their sins. The second one announces to them a therapy appropriate to the position they have identified. This therapy is supposed to be the baptism of repentance for the forgiveness of sins preached by John, equating with the future baptism in the Holy Spirit.